2021
DOI: 10.1002/chem.202102585
|View full text |Cite
|
Sign up to set email alerts
|

In‐Fjord Substitution in Expanded Helicenes: Effects of the Insert on the Inversion Barrier and Helical Pitch

Abstract: A series of expanded helicenes of different sizes and shapes incorporating phenyl-and biphenyl-substituents at the deepest part of their fjord have been synthesized via sequential Au-catalyzed hydroarylation of appropriately designed diynes, and their racemization barriers have been calculated employing electronic structure methods. These show that the overall profile of the inversions (energies, number of transition states and intermediates, and their relative position) is intensively affected by the interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Yashima and co-workers have shown that fusing multiple helical anthracenes together also effectively enables the separation of enantiomers, but these multiple helicenes display inferior | g abs | of ≤0.015 . Notably, the original expanded helicenes illustrated in Figure a have larger diameters than helical anthracenes (∼13.5 vs ∼11.5 Å), suggesting that they should show further improvement in | g abs |; however, a similar noncovalent locking strategy was attempted on such an expanded helicene that failed to provide configurational stability …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yashima and co-workers have shown that fusing multiple helical anthracenes together also effectively enables the separation of enantiomers, but these multiple helicenes display inferior | g abs | of ≤0.015 . Notably, the original expanded helicenes illustrated in Figure a have larger diameters than helical anthracenes (∼13.5 vs ∼11.5 Å), suggesting that they should show further improvement in | g abs |; however, a similar noncovalent locking strategy was attempted on such an expanded helicene that failed to provide configurational stability …”
Section: Introductionmentioning
confidence: 99%
“…32 Notably, the original expanded helicenes illustrated in Figure 1a have larger diameters than helical anthracenes (∼13.5 vs ∼11.5 Å), suggesting that they should show further improvement in |g abs |; however, a similar noncovalent locking strategy was attempted on such an expanded helicene that failed to provide configurational stability. 33 Lengthening the helicene backbone also increases ΔG ‡ e , but this poses a considerable synthetic challenge. Since Newman's landmark synthesis of [6]helicene in 1956, 34 there has been significant effort devoted to this challenge.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 43–45 Since then, several expanded helicenes with unique spiral frameworks have been designed and synthesized, including expanded helicene‐based macrocycles ( II ), 46 a helical analogue of kekulene ( III ), 47 helical anthracenes ( IV ), 48,49 and in‐fjord‐substituted expanded helicenes ( V ) (Figure 1a). 50 …”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45] Since then, several expanded helicenes with unique spiral frameworks have been designed and synthesized, including expanded helicene-based macrocycles (II), 46 a helical analogue of kekulene (III), 47 helical anthracenes (IV), 48,49 and in-fjord-substituted expanded helicenes (V) (Figure 1a). 50 For the synthesis of expanded helicenes with a larger helical diameter than the corresponding classical helicenes, a substantial number of aromatic rings are required to be fused by intramolecular multifold cyclizations, which often afford a complicated product mixture due to incomplete cyclizations and/or undesired side reactions, resulting in low yields after a time-consuming isolation process. 43,[45][46][47][48][49][50] Therefore, the development of a novel synthetic approach for quantitatively producing expanded helicenes through a complete annulative π-extension of aromatization precursors is highly demanded for exploring an unexplored domain of helically twisted PAHs, which will provide a novel class of expanded helicenes with specific chiroptical, optical, electrochemical, and physical properties [43][44][45][46][47][48][49][50] inaccessible from the angularly fused typical single 17,18 and multiple [19][20][21][22][23] helicenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation